All Days 2008
DOI: 10.2118/116711-ms
|View full text |Cite
|
Sign up to set email alerts
|

A New Solution to Restore Productivity of Gas Wells With Condensate and Water Blocks

Abstract: During production from gas condensate reservoirs, significant productivity loss occurs after the pressure near the production wells drops below the dew point of the hydrocarbon fluid. Many of these gas reservoirs also have some water accumulation near the wells. This adds significantly to the total liquid blocking. Experiments were conducted using both outcrop sandstone and reservoir cores to measure the effect of liquid blocking on gas relative permeability. A chemical treatment was develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…The idea of wettability alteration for gas-oil systems was first proposed by Li and Firoozabadi (2000). Since then, extensive experimental studies have been dedicated to this subject with the main concentration on finding appropriate wettability modifiers for sandstone substrates (Kumar et al, 2006;Panga et al, 2006;Fahes and Firoozabadi, 2007;Bang et al, 2008). There are limited number of CT field trials in sandstone gas-condensate reservoirs reported with promising (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The idea of wettability alteration for gas-oil systems was first proposed by Li and Firoozabadi (2000). Since then, extensive experimental studies have been dedicated to this subject with the main concentration on finding appropriate wettability modifiers for sandstone substrates (Kumar et al, 2006;Panga et al, 2006;Fahes and Firoozabadi, 2007;Bang et al, 2008). There are limited number of CT field trials in sandstone gas-condensate reservoirs reported with promising (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The mobility zone near the wellbore is the region of interest in this study. In order to overcome this problem, procedures like hydraulic fracturing or solvent injection can be considered with the objective to decrease interfacial tension and increase liquid vaporization rate (Bang et al 2008). Another approach has been proposed, altering wettability of the system to intermediate gas-wetting.…”
Section: Introductionmentioning
confidence: 99%
“…These tests were also performed at reservoir conditions. Bang et al (2008) conducted experiments at reservoir temperature and pressure with a different set of mixtures. L19945 was mixed with 2-butoxyethanol (EGMBE) and ethanol, which showed an increase in oil and gas relative permeability of a factor of more than 2.…”
Section: Introductionmentioning
confidence: 99%
“…This method is based on reducing the liquid-wetting of the rock surface to enhance liquid mobility and reduce the accumulation of liquid condensate. A few other research groups at universities and companies have also been investigating this method (Bang et al, 2010;Ahmadi et al, 2010;Al-Anazi et al, 2007;Zheng and Rao, 2010). Pilot tests were also conducted in recent years (Butler et al, 2009;Liu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The authors believe that the low permeability of the reservoir could be one of the main reasons for the failure. In another field application in 2009, a team from Trueblood Resources Inc., The University of Texas at Austin and 3M Company conducted a chemical treatment for a gas-condensate reservoir (Bang et al, 2010). The average permeability was 20 md and the reservoir pressure was 2971 psi.…”
Section: Introductionmentioning
confidence: 99%